Microstructure transformation of undercooled Cu-Ni-Co Alloy and refinement mechanism under high undercooling - An Hongen; Liew, Willey Yun Hsien; Nancy Julius Siambun; Chua, Bih Lii; Yang Mengmeng; Yan Wei; Li Hongtao (Springer Nature, 2023)
The molten Cu60Ni35Co5 ternary alloy was undercooled by fluxing method and solidified by natural cooling method. The microstructure of all undercooled samples were analyzed. It is found that the rapidly solidified Cu60Ni35Co5 alloy has undergone two grain refinement phenomena within the undercooling range, and its microstructure and morphology change with the undercooling through the transformation process of “coarse dendrite - equiaxed dendrite - oriented fine dendrite - equiaxed crystal”. The refined structure with the maximum undercooling ∆T of 253 K was selected for electron backscatter diffraction (EBSD) and transmission electron microscopy (TEM) tests. EBSD results show that the refined structure contains a high proportion of large angle grain boundaries (LAGBs), a large number of randomly oriented grains, and high proportion of twins, while TEM results show that the dislocation density in most areas is relatively low. The above characteristics confirm that the solidification structure is refined due to recrystallization behavior under high undercooling.